2020
DOI: 10.3390/plants9030353
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and Biochemical Characterization of Cytosolic Pyruvate Kinases in Arabidopsis thaliana

Abstract: Glycolysis is a central catabolic pathway in every living organism with an essential role in carbohydrate breakdown and ATP synthesis, thereby providing pyruvate to the tricarboxylic acid cycle (TCA cycle). The cytosolic pyruvate kinase (cPK) represents a key glycolytic enzyme by catalyzing phosphate transfer from phosphoenolpyruvate (PEP) to ADP for the synthesis of ATP. Besides its important functions in cellular energy homeostasis, the activity of cytosolic pyruvate kinase underlies tight regulation, for in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 35 publications
(63 reference statements)
2
27
0
Order By: Relevance
“…We found that CPK4/5/6/11 and MTP8 have similar expression patterns and are mainly expressed in whole young seedlings and in the leaves, seeds, and flowers of mature plants (Supplemental Figure 3A). In addition, previous research used GUS staining or RT-PCR to demonstrate that CPK4/5/6/11 are expressed mainly in roots, leaves, and cotyledons in the seedling stage (Zhu et al, 2007;Wulfert et al, 2020;Zhang et al, 2020). MTP8 is also mainly expressed in roots under Fe deficiency and its weak expression in cotyledons is not altered under Fe deficiency.…”
Section: Resultsmentioning
confidence: 99%
“…We found that CPK4/5/6/11 and MTP8 have similar expression patterns and are mainly expressed in whole young seedlings and in the leaves, seeds, and flowers of mature plants (Supplemental Figure 3A). In addition, previous research used GUS staining or RT-PCR to demonstrate that CPK4/5/6/11 are expressed mainly in roots, leaves, and cotyledons in the seedling stage (Zhu et al, 2007;Wulfert et al, 2020;Zhang et al, 2020). MTP8 is also mainly expressed in roots under Fe deficiency and its weak expression in cotyledons is not altered under Fe deficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Cytosolic phosphoenolpyruvate carboxykinase 1 (PCK1) could decarboxylate OAA to phosphoenolpyruvate [PEP ( 33 )]. PEP is then used either for gluconeogenesis or converted into pyruvate by pyruvate kinase [PK ( 34 )]. The accumulation of pyruvate strongly indicated that the cytosolic PK route is active in BHAC plants and that PEP is not channeled into gluconeogenesis, which was supported by reduced glucose and fructose levels in the same plants ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…28 Studies have shown that the putative underlying mechanisms of MUC5AC neo-expression include promotor hypomethylation. 11 MUC5AC transcription is also directly and indirectly regulated by various cancer-associated transcription factors (eg AP-1, SP-1, NF-kB, HNF-5a-alpha) and pathways (eg MAPK, Akt/ PI3K) [39][40][41] as well as by several mediators of inflammation (IL-1-beta, IL-6, TNF-alpha, IL-13). [41][42][43][44] Tumor types that are always MUC5AC negative are of diagnostic interest, because a positive MUC5AC immunostaining will virtually exclude such entities from diagnostic considerations.…”
Section: Discussionmentioning
confidence: 99%